Researching student learning in higher education : a social realist approach - Case, Jennifer M. (Abingdon, Oxon : Routledge/Taylor & Francis Group, 2013)
'Many contemporary concerns in higher education focus on the student experience of learning, battling with the dual concerns of a larger and much more diverse intake than ever before and the limitation of funding; questions are being asked afresh around the purposes of higher education. As much as the central questions in higher education focus on student enrolment in programmes, student retention, progression and success, graduate fitness for work, the actual student tends to be absent in so much of this rhetoric and even scholarly literature. The central questions are then of grading, selection, conversion and efficiency but these analyses have not really yielded much apart from providing some indication that the system is hugely inefficient. This book turns this conversation on its head, by inserting a full consideration of student participation into the context of higher education. Working sociologically, it explores the influence of the social context on what the individual student achieves. It utilises a social realist approach to researching student learning, illustrating its potential value by a detailed exploration of student learning within one particular discipline: engineering education'--
Includes bibliography : p. 147-155.
Keywords: Engineering -- Study and teaching (Higher) -- South Africa -- Case studies; College students -- Social conditions -- South Africa -- Case studies; Academic achievement -- Social aspects -- South Africa -- Case studies